2010
DOI: 10.1002/elps.200900689
|View full text |Cite
|
Sign up to set email alerts
|

Separation of phenolic acids and flavone natural antioxidants by two‐dimensional method combining liquid chromatography and micellar electrokinetic capillary chromatography

Abstract: A 2‐D method was developed for separation of phenolic acids and flavone compounds combining LC with MEKC. The effect of substituted neutral and anionic CD additives to the background electrolyte on the quality of MEKC separation was investigated. The best selectivity of the MEKC separation was achieved in 25 mmol/L borate background buffer at pH 9.05 with the addition of 10 g/L SDS and 1.85 g/L heptakis (6‐O‐sulfo)‐β‐CD. These conditions were used in the second dimension of 2‐D combination of LC and MEKC separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…The analysis of phenolic compounds is one of the main applications of CE in food analysis as can be deducted from the number of published works 47–71. The main food matrices analyzed by CE for determining phenol, polyphenols and pigments in the period of time covered by this review were olive oils 47–53, tea 54–59 and wine 60–62.…”
Section: Phenols Polyphenols and Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of phenolic compounds is one of the main applications of CE in food analysis as can be deducted from the number of published works 47–71. The main food matrices analyzed by CE for determining phenol, polyphenols and pigments in the period of time covered by this review were olive oils 47–53, tea 54–59 and wine 60–62.…”
Section: Phenols Polyphenols and Pigmentsmentioning
confidence: 99%
“…For instance, Chi et al developed a CZE method with amperometric detection (AD) in which the phosphate buffer contained β‐cyclodextrin for the simultaneous determination of kaempferol, apigenin, rutin, quercetin, luteolin and ferulic acid in Chinese herbal tea 56. Cesla et al demonstrated the suitability of an offline 2D system combining HPLC (first dimension) and MEKC separation in borate buffer with SDS and heptakis‐(6‐ O ‐sulfo)‐β‐cyclodextrin (second dimension) for the separation of 25 flavone compounds and phenolic acids 57. On the other hand, Li et al described for the first time, the use of microwave‐assisted extraction followed by CZE‐UV for the fast analysis of cathequin and epicatechin in green tea 58.…”
Section: Phenols Polyphenols and Pigmentsmentioning
confidence: 99%
“…Comprehensive 2D LC has been established as a separation method suitable for analysis of highly complex samples of food and natural products , metabolites , biopolymers , and other analytes [8,9]. Off‐line and on‐line combinations of LC in one dimension with electromigration separations in the second one have been introduced . The electromigration methods are generally likely to provide narrow peaks and hence high peak capacity.…”
Section: Introductionmentioning
confidence: 99%
“…LC may also be combined with alternative separation methods. For example, Cesla et al 151 recently reported an interesting off‐line 2‐D method combining LC and micellar electrokinetic capillary chromatography (MEKC) for the analysis of 25 phenolic acids and flavone standards. In this set‐up, fractions from the first‐dimension HPLC column (Discovery HS PEG) were automatically collected using a CE autosampler, which was programmed to rotate every 15 s. The collected fractions were subsequently analysed by MEKC using a background electrolyte containing 25 mM borate buffer (pH 9.05), 10 g/L SDS and 1.85 g/L heptakis(6‐ O ‐sulfo)‐β‐CD on a 48 cm capillary.…”
Section: Applications Of Recent Advances In Hplc To Phenolic Analysismentioning
confidence: 99%